Automation Architecture for Bayesian Network Based Test Case Prioritization and Execution - Ufuktepe, Ekincan; Tuğlular, Tuğkan; Ufuktepe, Ekincan; Tuğlular, Tuğkan (Institute of Electrical and Electronics Engineers Inc., 2016)
An automation architecture for Bayesian Network based test case prioritization is designed for software written in Java programming language following the approach proposed by Mirarab and Tahvildari [2]. The architecture is implemented as an integration of a series of tools and called Bayesian Network based test case prioritization and execution platform. The platform is triggered by a change in the source code, then it collects necessary information to be supplied to Bayesian Network and uses Bayesian Network evaluation results to run high priority unit tests.
2016 IEEE 40th Annual Computer Software and Applications Conference, COMPSAC 2016; Atlanta; United States; 10 June 2016 through 14 June 2016
Keywords: Bayesian Networks; Test prioritization; Network architecture; Unit testing